Productivity of IPB-D2 and IPB-D3 Chickens with Repeatability of Newcastle Disease Antibody Titer - Ratnawati, Diana; Sri Darwati; Murtini, Sri; Sumantri, Cece (Jurnal Ilmu Pertanian Indonesia, 2025)
ND virus causes mortality in poultry. Passively acquired maternal antibodies inhibit immunoglobulin formation. Repeatability is a genetic parameter that determines the inheritance of traits from elders to chicks. IPB-D2 chickens were selected for disease resistance, and IPB-D3 chickens were selected for weight gain. This study aimed to evaluate the productivity of IPB-D2 and IPB-D3 chickens and assess the inheritance of Newcastle Disease (ND) antibody traits in 36 IPB-D3 and 21 IPB-D2 chickens. The T-test was used to compare the group means of the two chicken breeds. Antibody titer measurements were based on the Geometric Mean Titer (GMT). Estimation of ND titer repeatability using within-class correlation. Fertility and hatchability differed significantly (p < 0.05). ND titer of IPB-D2 chicken and IPB-D3 chicken DOC LOG 2 GMT 1.61 ± 1.10 and 1.34 ± 0.95. The antibody titer of IPB-D2 and IPB-D3 chickens at 14 days of age was 1.02 ± 1.20 and 1.37 ± 0.95. The ND titer value in the egg yolk of IPB-D2 chicken was 4.02 ± 1.94, and in IPB-D3 chicken was 3.64 ± 2.54. The results showed the repeatability value of l antibodies in IPB D-2 chickens and IPB D-3 chickens in DOC 0.49±0.30, 0.42±0.33 and 0.39±0.28; 0.25±0.15, respectively. Fertility and hatchability of IPB-D3 chickens were better than those of IPB-D2 chickens. The yolk ND titer of IPB-D2 chickens was higher than IPB- D3 chicken. The ND titer reciprocity of IPB-D2 chickens was higher than that of the IPB-D3 chickens. Keywords: IPB-D2 Chicken, IPB-D3 Chicken, Newcastle Disease, productivity, repeatability